2006
DOI: 10.1016/j.trstmh.2005.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Chagas’ disease in a patient with non-Hodgkin's lymphoma: gastric, oesophageal and laryngeal involvement

Abstract: Changes in the natural course of Trypanosoma cruzi infection have been associated with immunosuppression. We report here a case of the reactivation of Chagas' disease in a patient with non-Hodgkin's lymphoma with gastric, oesophageal and laryngeal involvement. This is the first report describing the involvement of the larynx by T. cruzi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 17 publications
0
9
0
5
Order By: Relevance
“…This may occur inadvertently, in cases in which the patient undergoes transplantation without knowing that he/she has Chagas disease (usually in asymptomatic individuals in non-endemic countries), or due to heart transplant as a result of Chagas-related cardiac damage. Recent studies have shown that recurrence of Chagas disease may also occur in patients with lymphoreticular neoplasias, especially acute lymphocytic leukemia or Hodgkin's disease [30]. One challenge of identifying Chagas disease in immunosuppressed patients is that sera conversion may not occur.…”
Section: Acute Chagas Disease In Immunocompromised Patients: Importanmentioning
confidence: 99%
“…This may occur inadvertently, in cases in which the patient undergoes transplantation without knowing that he/she has Chagas disease (usually in asymptomatic individuals in non-endemic countries), or due to heart transplant as a result of Chagas-related cardiac damage. Recent studies have shown that recurrence of Chagas disease may also occur in patients with lymphoreticular neoplasias, especially acute lymphocytic leukemia or Hodgkin's disease [30]. One challenge of identifying Chagas disease in immunosuppressed patients is that sera conversion may not occur.…”
Section: Acute Chagas Disease In Immunocompromised Patients: Importanmentioning
confidence: 99%
“…Even prior to the advent of the HIV/AIDS pandemic, reactivation of T. cruzi infection had been observed in patients undergoing immunosuppressive therapy for malignancies and organ transplantation [94–97]. Del Castillo et al [98] initially described a 19-year old man with hemophilia who had a hypodense lesion in the right frontal lobe.…”
Section: Chagas Disease and Immunosuppressionmentioning
confidence: 99%
“…1 Amplamente distribuída pelo continente americano acomete ao redor de 11 milhões de pessoas, com 3-5 milhões de infectados no Brasil. [1][2][3][4] A sua reativação em casos de imunossupressão grave tem sido amplamente demonstrada. 3,[5][6][7][8][9] Os relatos de reativação da DC em pacientes com neoplasias hematológicas comumente associam-se ao transplante de células-tronco hematopoéticas (TCTH) correlacionadas à imunossupressão devido à doença de base, terapia antitu-moral e regimes de condicionamento.…”
Section: Introductionunclassified
“…3,[5][6][7][8][9] Os relatos de reativação da DC em pacientes com neoplasias hematológicas comumente associam-se ao transplante de células-tronco hematopoéticas (TCTH) correlacionadas à imunossupressão devido à doença de base, terapia antitu-moral e regimes de condicionamento. 3 Escassos são os relatos de reativação da doença na vigência de quimioterapia de doença onco-hematológica não associada a TCTH. 3,10,11 O presente caso ilustra reativação da DC com comprometimento de sistema nervoso central em paciente em quimioterapia para linfoma não Hodgkin não relacionado à TCTH, com tardia detecção do parasita em sangue e líquido cefalorraquidiano (LCR) e desfecho fatal a despeito de tratamento.…”
Section: Introductionunclassified
See 1 more Smart Citation